She rides shotgun [videorecording (DVD)] - Harper, Jordan; Collins, Ben (Screenwriter); Piotrowski, Luke, 1981-; Egerton, Taron, 1989-; Heger, Ana Sophia; Yang, Rob; A'zion, Odessa; Lyons, David, 1976-; Lynch, John Carroll, 1963-; Garfield, Wyatt; Marsh, Joshua J.; Blanck Mass (Musician); et al. (Lionsgate, 2025)
"Marked for death by unrelenting enemies, Nate must now protect his estranged 11-year-old daughter, Polly at all costs. Shy, precocious, and wary of her father, Polly is swept up in Nate's dangerous plight as they flee to evade the corrupt sheriff and brutal leader of a gang who will stop at nothing to protect his criminal interests. With scant resources and no one to trust, Nate and Polly form a bond forged under fire as he shows her how to fight and survive--and she teaches him what unconditional love truly means."--